Colombia : Second Review Under the Stand-By Arrangement and Request for Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The program made good progress toward creating the conditions for faster sustained growth over the medium term. The economic policies aim to preserve the program's macroeconomic framework. Fiscal policy is expected to stay on a sustainable path. The central bank has been successful in achieving its inflation target. The proposed target for net international reserves will maintain an adequate reserve cushion. The prospects for sustained growth over the medium term remain favorable, provided the government maintains a strong fiscal policy and advance structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet